Can we sustain success in reducing deaths to extreme weather in a hotter world?. (June 2019) - Mehrabi, Zia; Donner, Simon; Rios, Patricia; Guha-Sapir, Debarati; Rowhani, Pedram; Kandlikar, Milind; Ramankutty, Navin
Abstract: In an incredible story of human adaptation, the aggregate global risk of mortality to extreme weather declined by over two orders of magnitude over the past century. Yet the data show that large losses of lives to extreme weather disasters persist in nations typified by poor economic development, weak institutions, and political instability. And currently we are seeing spikes in mortality from extreme heat events in rich nations, including a wave of new reported deaths in Japan, Europe, and Canada during 2018. These events and future projections of increasing exposure suggest that we need to revisit adaptation strategies to deal with the adverse effects of extreme weather disasters across the world.